N = 2 higher spins: superfield equations of motion, the hypermultiplet supercurrents, and the component structure - Buchbinder, Ioseph L. (Journal of high energy physics)
As a continuation of our previous papers arXiv:2109.07639 and arXiv:2202.08196, we study the linearized structure of the manifestly 4D, N = 2 supersymmetric theory of the cubic couplings of the higher spin gauge superfields to the matter hypermultiplets. We consider in detail the superfield equations of motion, construct the conserved hypermultiplet superfield currents, explore their component structure (basically in the bosonic sector) and compare it with the corresponding currents in the conventional higher-spin bosonic theory. We thoroughly study the N = 2 spin 2 and 3 models as instructive examples.